Countermeasures for Sirri Marriage in Samarinda City: The Role of Religious Leaders with the Concept of Sadd Adz-Dzari'ah: - Mohammad Syahrul Wardana (Legitima : Jurnal Hukum Keluarga Islam, 2021)
Sirri marriage is a marriage that only fulfills the terms and conditions of Islam and is not registered in the Office of Religious Affairs (KUA) which can have the impact of neglecting the rights of children and wives, so that based on the 2008 MUI Fatwa stipulates that sirri marriage is declared haram. Moreover, by looking at the number of nikah sirri which is still relatively high in Samarinda City in the annual report of the Samarinda Religious Court in 2016-2020. This research is an empirical juridical research that uses facts in the field, data on nikah sirri in the Samarinda Religious Court, MUI fatwas and the opinions of scholars. So that it can be seen how the attitude and role towards nikah sirri. The results of this study are, First, the data on nikah sirri obtained from the Samarinda Religious Court in 2016-2020 has registered as many as 944 cases of filing for isbat nikah. Most religious leaders interpret that nikah sirri is only legal in religion but not in the state. Second, religious leaders who realize that they actually do not have the rights and obligations given by state leaders, agree to refuse to marry people in a sirri manner and conduct education to provide knowledge about the impact of sirri marriage which can harm their wives and children in the future.